IMPROVING NURSES’ KNOWLEDGE AND PRACTICES OF SAFE INJECTION AT CHILDREN’S HOSPITAL 1 IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge and practices of safe injection among nurses at Children’s Hospital 1, as well as identify factors influencing their adherence to safe injection protocols.Method: A cross-sectional descriptive study was conducted using a combination of questionnaire surveys and direct observation. A total of 100 nurses were surveyed regarding their knowledge and practices of safe injection. In-depth interviews were conducted with 10 nurses to further explore challenges in following the protocols.Results: 68% of nurses had adequate knowledge of safe injection practices, but only 38% adhered to the full protocol. Compliance was higher for pre-injection practices (75%) compared to practices during injection (60%) and post-injection (50%). Key factors influencing adherence included knowledge, work experience, and support from hospital leadership. Interviews revealed that challenges such as lack of equipment and high workload contributed to difficulties in maintaining compliance.Conclusion: Continuous training, improved equipment availability, and regular monitoring systems are necessary to enhance the quality of safe injection practices at the hospital.
Keywords: Injection safety, nurses, Children’s Hospital 1.